Análisis del concepto de coaching de salud - Higuera-Sainz, José Luis (Universidad de Sonora, 2019)
Introduction: Coaching in the health sector or Health Coaching is a new field that has emerged as a basic need for health care; however, there is little information about its definition, attributes, and usefulness. Objective: analyze the concept of Health Coaching through a review of information capable of developing a useful and applicable proposal for health professionals and health coaches who practice it. Methodology: For the review of the information and literature, the databases which were consulted are the following: LILACS, COCHRANE, EBSCO, PUB MED, Scielo electronic library, and the Google academic search engine using the keywords: coaching and health in English, Spanish and Portuguese languages. Results: During the analysis, information or investigations with open access were included all of which evidenced the meaning of the concept. Conclusion: the search and analysis of information and literature allowed us to identify the concept as a methodological process where a health professional with training in coaching, accompanies other people through an empathic and collaborative relationship to set and fulfill objectives specifically related to health.